2023
DOI: 10.3390/microorganisms11020434
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthetic Gene Clusters from Swine Gut Microbiome

Abstract: The abuse of antibiotics has become a serious health challenge in the veterinary field. It creates environmental selection pressure on bacteria and facilitates the rapid spread of antibiotic resistance genes. The speed of discovery and application of cost-effective alternatives to antibiotics is slow in pig production. Natural products from biosynthetic gene clusters (BGCs) represent promising therapeutic agents for animal and human health and have attracted extraordinary passion from researchers due to their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Aryl polyenes, which are structurally similar to carotenoids, have also been reported to protect cells from damage caused by reactive oxygen species and promote biofilm formation by EPS in E. coli . EPS production by M. xanthus is important for smooth S cell movement and colony formation (Johnston et al, 2021; L. Wang et al, 2023). These results suggest that Myxococcota in activated sludge use bacteriocins during OME to avoid grouping with different species and promote EPS production.…”
Section: Resultsmentioning
confidence: 99%
“…Aryl polyenes, which are structurally similar to carotenoids, have also been reported to protect cells from damage caused by reactive oxygen species and promote biofilm formation by EPS in E. coli . EPS production by M. xanthus is important for smooth S cell movement and colony formation (Johnston et al, 2021; L. Wang et al, 2023). These results suggest that Myxococcota in activated sludge use bacteriocins during OME to avoid grouping with different species and promote EPS production.…”
Section: Resultsmentioning
confidence: 99%
“…Natural products from the gut microbial biosynthetic gene cluster represent promising therapeutic agents for animal and human health 48 . Combined with the whole-genome sequencing analysis and metabolomics analysis of extra- and intracellular LGG, we found that the extracellular proline level in LGG was increased under nucleoside pressure by proline excretion genes ( proW , proV ).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have revealed species-speci c, uncharacterized small-molecule-encoding BGCs in the gut microbiome of humans 21 , swine 49 , and ants 50 . Most of the BGCs are always enriched in the members of gut-associated bacteria, such as Bacteroides, Parabacteroides, and Ruminococcus, and the chemical classes from the gut microbiota exhibit notable differences compared to non-gut-associated bacteria 21 .…”
Section: Discussionmentioning
confidence: 99%